2021
DOI: 10.3390/ma14164406
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Adhesion Performance of Asphalt-Calcium Silicate Hydrate Gel Interface in Semi-Flexible Pavement Materials Based on Molecular Dynamics

Abstract: The interface between an asphalt binder and a calcium silicate hydrate (C-S-H) gel is a weak point of semi-flexible pavement material. In this study, the adhesion performance of asphalt-C-S-H gel interface in semi-flexible pavements at a molecular scale has been investigated. Molecular dynamics (MD) simulations were applied to establish three asphalt binders: 70# asphalt binder (the penetration is 70 mm), PG76-22 modified asphalt binder (a kind of asphalt binder that can adapt to the highest temperature of 76 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…When the automobile exhaust gas is adsorbed in the TiO 2 channel, the two independent systems of vehicle exhaust and TiO 2 gradually become a whole system, and refer to other systems, the reduction of system energy is considered as the adhesion work [ 40 ]. In other words, the adhesion work is the difference between the total energy of a whole-body (formed by adsorption of automobile exhaust and TiO 2 ) and the sum of the surface energy of vehicle exhaust and TiO 2 respectively before adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…When the automobile exhaust gas is adsorbed in the TiO 2 channel, the two independent systems of vehicle exhaust and TiO 2 gradually become a whole system, and refer to other systems, the reduction of system energy is considered as the adhesion work [ 40 ]. In other words, the adhesion work is the difference between the total energy of a whole-body (formed by adsorption of automobile exhaust and TiO 2 ) and the sum of the surface energy of vehicle exhaust and TiO 2 respectively before adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…The four representative molecules are asphaltene (C 149 H 177 N 3 O 2 S 2 ), resin (C59H85NOS), aromatic (C46H50S), and saturate (C 22 H 46 ), as shown in Figure 2 . The proportion of the four representative molecules in this model is calculated according to the mass ratio and molecular weight of each component in asphalt, in line with previous studies [ 36 , 37 ], as shown in Table 1 .…”
Section: Simulationmentioning
confidence: 93%
“…It was obvious that both aggregates can adsorb ABA, but the gradient of the concentration distribution was different. The essence of the concentration curve is the uniformly spaced atomic density curve [48], which can characterize the degree of molecular aggregation at a certain distance [45]. The z-direction distribution of ABA on the surface of SiO 2 was uniform, while the distribution on the surface of CaCO 3 was uneven, especially the atomic density near the surface of the aggregate was higher, so that the adsorption of asphalt was stronger with CaCO 3 .…”
Section: Interaction Behavior Of Virgin and Short-term Aged Asphalt-a...mentioning
confidence: 99%